Microbial colonization patterns predict the outcomes of surgical treatment of intrabony defects - Lisa Heitz-Mayfield (Blackwell Synergy, 2006)
Aim: To explore the impact of bacterial load and microbial colonization patterns on the clinical outcomes of periodontal surgery at deep intrabony defects. Materials and Methods: One hundred and twenty-two patients with advanced chronic periodontitis and at least one intrabony defect of 43mm were recruited in 10 centres. Before recruitment, the infection control phase of periodontal therapy was completed. After surgical access and debridement, the regenerative material was applied in the test subjects, and omitted in the controls. At baseline and 1 year following the interventions, clinical attachment levels (CAL), pocket probing depths (PPD), recession (REC), full-mouth plaque scores and full-mouth bleeding scores were assessed. Microbial colonization of the defect-associated pocket was assessed using a DNA–DNA checkerboard analysis. Results: Total bacterial load and counts of red complex bacteria were negatively associated with CAL gains 1 year following treatment. The probability of achieving above median CAL gains (43 mm) was significantly decreased by higher total bacterial counts, higher red complex and T. forsythensis counts immediately before surgery. Conclusions: Presence of high bacterial load and specific periodontal pathogen complexes in deep periodontal pockets associated with intrabony defects had a significant negative impact on the 1 year outcome of surgical/regenerative treatment.